Anti-inflammatory Properties of Mitragyna Speciosa Extract - Aziddin R.E, Raja; M.R, Mustafa; Z, Mohamed; M.A, Mohd. (Malaysian Journal of Science, 2005)
The anti-inflammatory property of the alkaloid extract from the leaves of Mitragyna speciosa was evaluated on the basis of the inhibitory effect of the extract on carrageenan-induced hind paw edema in rat. This extract when administered by intra peritoneal injection at a concentration of 50 mg/kg produced almost 100% inhibition of the carrageenan-induced paw edema 1 hour after administration. The inhibition was maintained at about 60%, 7 hours after administration. These findings suggest that the alkaloid extracts of the leaves of Mitragyna speciosa possess potent anti-inflammatory properties.